2000
DOI: 10.1037/0278-6133.19.1.91
|View full text |Cite
|
Sign up to set email alerts
|

Physician-diagnosed medical disorders in relation to PTSD symptoms in older male military veterans.

Abstract: The association between physician-diagnosed medical disorders and combat-related posttraumatic stress disorder (PTSD) symptoms was examined in 605 male combat veterans of World War II and the Korean conflict. Physician exams were performed at periodic intervals beginning in the 1960s. PTSD symptoms were assessed in 1990. Cox regression was used to examine the onset of each of 12 disorder categories as a function of PTSD symptoms, controlling for age, smoking, alcohol use, and body weight at study entry. Even w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
201
3
6

Year Published

2004
2004
2015
2015

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 256 publications
(223 citation statements)
references
References 21 publications
(33 reference statements)
12
201
3
6
Order By: Relevance
“…15 Other studies have demonstrated that the increase in health services utilization in veterans with PTSD is not due to comorbid psychiatric conditions, such as anxiety and depression. 26,27 Our study adds to this prior research by using national-level data, adjusting for several additional military service characteristics, and exploring utilization in OEF/OIF veterans, a group for which data are very limited. 6 There are several possible explanations for our finding of increased utilization of non-mental health services in OEF/OIF veterans with mental disorders, particularly PTSD.…”
Section: Discussionmentioning
confidence: 99%
“…15 Other studies have demonstrated that the increase in health services utilization in veterans with PTSD is not due to comorbid psychiatric conditions, such as anxiety and depression. 26,27 Our study adds to this prior research by using national-level data, adjusting for several additional military service characteristics, and exploring utilization in OEF/OIF veterans, a group for which data are very limited. 6 There are several possible explanations for our finding of increased utilization of non-mental health services in OEF/OIF veterans with mental disorders, particularly PTSD.…”
Section: Discussionmentioning
confidence: 99%
“…chest tightness and shortness of breath), making it difficult to distinguish between these two conditions. Correspondingly, male combat veterans with PTSD did not have more commonly physician-diagnosed pulmonary diseases than those without PTSD [21], and the agreement between patients' and physicians' reports of respiratory dysfunction was low in Vietnam veterans independent of their PTSD status [22]. Thirdly, traumatic experiences and PTSD, respectively, have not yet been related to objective measures of lung function.…”
mentioning
confidence: 91%
“…There is a substantial literature on the physical health of veterans that documents a high prevalence of poor health, functional limitation, and disability (Aldwin et al 1994;Beebe 1975;Centers for Disease Control 1998;Keehn 1980;Schnurr et al 2000). Service members and veterans who were deployed to war zones are more likely to report ill health and chronic fatigue, gastrointestinal diseases, skin disorders, and chronic pain (Armed Forces Health Surveillance Center 2009;Institute of Medicine 2008).…”
Section: Military Service and Physical Healthmentioning
confidence: 99%